The seismic performance of braced timber pile bents. - Shama, Ayman A. (Earthquake engineering & structural dynamics.)
The seismic performance of timber bridge substructures is not well established, particularly when compared to concrete highway bridges. This paper presents a dual experimental computational modelling program to investigate the seismic behaviour of typical braced timber bridge pile bents. For this purpose, a prototype timber bridge was used to develop a near full size physical model that was used for shaking table experiments and quasi static reversed cyclic loading tests on the laboratory strong floor. A non linear force displacement computational modelling study was also undertaken as a companion effort to the experimental investigation. On the basis of the experimental study, seismic vulnerability analysis was conducted for this kind of timber bridge principally with shaking in the transverse direction. In this analysis, a simplified fundamental mechanics-based approach was employed from which fragility curves were denied. The study showed that braced timber pile bents have considerable strength and deformability capability.